STUDI HAMBATAN DAN KECEPATAN KAPAL TIPE LAMBUNG SERIES 60 DITINJAU DARI TIGA BENTUK HALUAN KAPAL - Suranto, Purwo Joko (Bina Teknika, 2016)
Research that has been done resulting hull of Series 60 is one model of ship hulls. Series 60 hull is used for the a merchant ship to block coefficient range from 0.65 - 080. Research Series 60 hull has great success, the American Towing Tank Conference (ATTC) and the International Towing Tank Conference (ITTC) agreed to fund further research for the Series 60 hull. The results of further research, published by the Society of Naval Architects and Marine enginners (SNAME). hull form series 60 is still widely used for type of commercial ships due to have a midship U is almost square so that traffic carried quite a lot of it is important for commercial ships, in addition to stability is also good. The bow of a ship is part of the greatest pressure and voltages, as the brunt of the water and the ship blows waves. Modeled and analyzed Series 60 Hull with a sloping shape of the bow, the bulbows and X-Bow with the main dimension of the vessel : Lpp = 30.97m, B = 4.34m, T = 1.7m. To further analyze the effect of the three forms of the bow ship for resistance and speed. Analyzed to three forms of the hull at speeds of 0 to 8.25 knots have resistance almost flat at around 7000 Newton, meaning the ship relatively similar obstacles. At speeds above the 8.25 knots have resistance vessel with a hull tilted began to increase with increasing vessel speed has become increasingly apparent obstacles ships is increasing drastic, especially at a speed of 30 knots have resistance of ship 257733 Newton when compared with resistance vessel for bulbows form who is resistance 230059 Newton or X-bow have resistance 228943 Newton.